1979
DOI: 10.1139/f79-159
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Preference of Several Species of Salmo and Salvelinus and Some of Their Hybrids

Abstract: Temperature preference of newly feeding fry of two species of Salmo, three species of Salvelinus, and seven hybrids were determined in a horizontal gradient. Fry of species in the genus Salmo and intergeneric hybrids with female parent in Salmo selected significantly higher temperatures (13.0–15.0 °C, P < 0.05) than did fry of species and hybrids of the genus Salvelinus (9.0–11.5 °C). No significant differences were obtained among species and hybrids within either of the two groups described above. Preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…In experimental studies, juvenile Arctic charr demonstrate clear temperature preferences, moving into areas closer to their preferred temperature when given the opportunity (Peterson et al, 1979;Larsson, 2005). A tagging study reported by Rikardsen et al (2007) suggested anadromous Arctic charr also show some degree of temperature preference in the wild, as fish maintained a relatively narrow range of mean daily temperatures while in the marine environment (mean ± SD: 10.7 ± 0.66°C).…”
Section: Discussionmentioning
confidence: 96%
“…In experimental studies, juvenile Arctic charr demonstrate clear temperature preferences, moving into areas closer to their preferred temperature when given the opportunity (Peterson et al, 1979;Larsson, 2005). A tagging study reported by Rikardsen et al (2007) suggested anadromous Arctic charr also show some degree of temperature preference in the wild, as fish maintained a relatively narrow range of mean daily temperatures while in the marine environment (mean ± SD: 10.7 ± 0.66°C).…”
Section: Discussionmentioning
confidence: 96%
“…Baldwin (1956) maintained brook charr yearlings at four temperatures (9, 13, 17, and 21"C), finding maximum growth and food consumption at 13°C. McCormick et al (1972) showed that tmperatures between 9.8 and 15.4" C were suitable for growth and survival of brook charr during the first 8 weeks of life, the optimum lying between 12.4 and 15.4" C. Mortality rates were maximum between 17.9 and 19.5" C. Peterson et al (1979) reported that emerging brook charr (mean length 25-29 mm) preferred temperatures of 8.0 to 11.5"C while fingerlings (mean length 65mm) selected 17.5"C. Fry (1947) showed that preferred temperatures may correspond to thermal optima for physiological functions Temperature may account for the pronounced drop in feeding activity and ration in the Matamek River during late summer. Water temperature reached 19-22" C in the Matamek from mid-July to mid-August, attaining a critical level for the growth and survival of age-0 brook charr (McCormick et al 1972, Hokanson et al 1973, Dwyer et al 1983).…”
Section: Discussionmentioning
confidence: 98%
“…Brook trout prefer temperatures under 16°C, above which growth rates decrease (McCormick et al, 1972;Meehan & Bjornn, 1991). Mortality increases at temperatures above 18°C (Peterson et al, 1979), and the upper lethal limit for brook trout is approximately 25°C (Hynes, 1970;McCormick et al, 1972;Power, 1980). In the 90% BAH sections, stream temperatures regularly exceeded 20°C with temperatures as high as 24.5°C observed (Fig.…”
Section: Canopy Cover and Temperaturementioning
confidence: 99%